060 CORONARY ROTATIONAL ATHERECTOMY USING BURR-TO-ARTERY RATIOS OF LESS THAN 0.5 IS ASSOCIATED WITH LOW LEVELS OF COMPLICATIONS, HIGH PROCEDURAL SUCCESS RATES AND FAVOURABLE 12-MONTH OUTCOMES. (24th May 2013) - Brown, A J; Joshi, F R; Cacciottolo, P; Hoole, S P; Braganza, D M; Schofield, P M; West, N E J; Clarke, S C
Abstract : Background: Rotational atherectomy (RA) is an established treatment of heavily-calcified coronary stenoses. Previous data suggest higher procedural complication rates when Burr-to-Artery (BTA) ratios exceed 0.7; the manufacturer-recommended BTA being 0.6. Little contemporary data exists regarding safe and optimal burr sizing, which may be important when considering RA via the radial approach with lower-caliber guiding catheters. Methods: Single-centre retrospective review of patients undergoing elective RA between 2004 and 2011. Procedural success was defined as successful stent deployment with residual stenosis <30%, and complications defined as death, pericardial effusion/tamponade, coronary dissection/perforation and emergent CABG. Demographic and outcome data were obtained from local/national databases and casenote review. Quantitative coronary angiographic analysis was performed on archived films. Results: Elective RA was successful in 197/220 cases (89.5%) with 72% of cases male and 22% diabetic (mean age 71.1±8.9 years). Target vessel was LAD (50.9%), RCA (35.0%), LCx (10.9%) and LMS (3.2%). Mean reference diameter was 3.45±0.6 mm and mean diameter stenosis (DS) 71.9±12.9%. Maximum burr size/case ranged from 1.25–2 mm (mode 1.5 mm) with mean BTA 0.43±0.08. 10 procedural complications occurred (4.5%); one wire fracture, two dissections, three perforations, two emergency CABG, one unretractable burr and one death. No difference in mean BTA was observed between procedures with/without complications (0.38±0.03 vs 0.43±0.08; p=0.33), but residual DS was higher in those with complications (12.3±21.2 vs 58.8±31.2; p<0.01). No correlation was observed between maximum burr size and age, sex, DS or minimum luminal diameter. At 36-month follow-up mortality was 11.7% and target vessel revascularisation (TVR) 22.8%. Conclusions: Elective RA with low BTA is associated with high procedural success and low complication rates. These data imply that elective RA with a lower BTA than recommended is both safe and effective and need not preclude a transradial approach.